THE INFLUENCE OF PROPOLIS GIVING TO THE GUPPY FISH SEX REVERSAL (Poecilia reticulata) SOAKING METHOD WITH BROODSTOCK - Iman Nurzaman; Netti Aryani; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study was to determine the effect of propolis on the sex reversal of Guppy fish (Poecilia reticulata) with broodstock immersion method in a range of 24 hours and a different dose. This study was conducted over 80 days, performed at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Science, University of Riau. The experimental design used was a completely randomized design (CRD) with 1 factor of 4 treatments and 3 replications the P0 treatment (control), treatment P1 (0.2 ml), treatment P2 (0.4 ml) and P3 treatment (0.6 ml). The variables measured were Survival (SR), Briefing Gender Male, Weight Absolute Growth, Growth Absolute length and Growth Daily. The results showed that the direction of the male gender is the highest in the P2 treatment (0.4 ml) with the percentage of males was 72%, survival rate (SR) were highest in treatment P3 (85%) at a dose of 0.6 ml, where as growth absolute weight of 0.27 grams (P0), the absolute growth in length by 2.87 cm (P0 and P1) and daily weight growth rate of 2.84% (P0).Key word: Guppy, Propolis, Sex Reversal, Male